1999
DOI: 10.1038/sj.bjc.6690591
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the cytotoxicity of thymidylate synthase (TS) inhibitors by dipyridamole analogues with reduced α 1-acid glycoprotein binding

Abstract: Summary Dipyridamole has been shown to enhance the in vitro activity of antimetabolite anticancer drugs through the inhibition of nucleoside transport. However, the clinical potential of dipyridamole has not been realized because of the avid binding of the drug to the plasma protein α 1 -acid glycoprotein (AGP). Dipyridamole analogues that retain potent nucleoside transport inhibitory activity in the presence of AGP are described and their ability to enhance the growth inhibitory and cytotoxic effects of thymi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Accordingly, a number of compounds with potency comparable to that of DP, but only limited susceptibility to the effects of AGP, have been identified. Compounds 40 , 55 , 67 , and 73 have been shown to prevent thymidine rescue from the cytotoxic effects of the thymidylate synthase inhibitor nolatrexed in vitro, with 40 proving at least equipotent with DP in these resistance modulation experiments . Compounds 37 , 40 , and 41 have also been the subject of further detailed biological evaluation, which has shown that they can overcome the ability of thymidine and hypoxanthine to prevent the growth inhibitory activity of the new antifolate drug pemetrexed (MTA) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a number of compounds with potency comparable to that of DP, but only limited susceptibility to the effects of AGP, have been identified. Compounds 40 , 55 , 67 , and 73 have been shown to prevent thymidine rescue from the cytotoxic effects of the thymidylate synthase inhibitor nolatrexed in vitro, with 40 proving at least equipotent with DP in these resistance modulation experiments . Compounds 37 , 40 , and 41 have also been the subject of further detailed biological evaluation, which has shown that they can overcome the ability of thymidine and hypoxanthine to prevent the growth inhibitory activity of the new antifolate drug pemetrexed (MTA) .…”
Section: Discussionmentioning
confidence: 99%
“…Compounds 40, 55, 67, and 73 have been shown to prevent thymidine rescue from the cytotoxic effects of the thymidylate synthase inhibitor nolatrexed in vitro, with 40 proving at least equipotent with DP in these resistance modulation experiments. 44 Compounds 37, 40, and 41 have also been the subject of further detailed biological evaluation, which has shown that they can overcome the ability of thymidine and hypoxanthine to prevent the growth inhibitory activity of the new antifolate drug pemetrexed (MTA). 1 Their ability to reverse thymidine and hypoxanthine rescue was directly related to their NT inhibitory potency (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The studies aimed at improved activity or applicability compared to Dipy, for instance, in cancer-therapeutic use of analog RA25 (61a) (13WOP37129). Regarding nucleoside transport inhibition, remarkable effects have been found with ring homolog 113b and open-chain dialkylamino analog 226 (07JME3906, 13MI1), subst.-benzylamino compounds 124a, 208, and 227 (01MI1, 04JME4905), 208 derivative 209 and prodrug 210 (09MI1, 11JME1847), and alkoxy compounds, such as 189a and 228 (99MI2). Protected Dipy analog 128 was coupled through the amino group to give fluorescein conjugate 129 as a novel equilibrative nucleoside transport probe (11BCC1221).…”
Section: Dipyridamole Analogsmentioning
confidence: 99%
“…We used a modified rapid mixing technique, combined with an inhibitor-stop method, to determine thymidine uptake into L1210 murine leukemia cells, as described previously (14,17 3 H]thymidine in the extracellular space that was carried through the oil layer.…”
Section: Thymidine Transport Assaysmentioning
confidence: 99%
“…As part of a program to develop potent pyrimidopyrimidine analogues of dipyridamole with reduced AGP binding, we have optimized our initial lead compound, NU3076, a pyrimidopyrimidine that has comparable potency to dipyridamole without being affected by AGP (14) . Several analogues that inhibit nucleoside transport even in the presence of physiologic concentrations of AGP were identified (15).…”
Section: Introductionmentioning
confidence: 99%